Ionic Liquids Can Permanently Modify Porous Silicon Surface Chemistry. Issue 33 (12th July 2016) - Trivedi, Shruti; Coombs, Sidney G.; Wagle, Durgesh V.; Bhawawet, Nakara; Baker, Gary A.; Bright, Frank V.
Abstract: To develop ionic liquid/porous silicon (IL/pSi) microarrays we have contact pin‐printed 20 hydrophobic and hydrophilic ionic liquids onto as‐prepared, hydrogen‐passivated porous silicon (ap‐pSi) and then determined the individual IL spot size, shape and associated pSi surface chemistry. The results reveal that the hydrophobic ionic liquids oxidize the ap‐pSi slightly. In contrast, the hydrophilic ionic liquids lead to heavily oxidized pSi (i.e., ox‐pSi). The strong oxidation arises from residual water within the hydrophilic ILs that is delivered from these ILs into the ap‐pSi matrix causing oxidation. This phenomenon is less of an issue in the hydrophobic ILs because their water solubility is substantially lower. Abstract : Put on the spot : To develop ionic liquid/porous silicon (IL/pSi) microarrays 20 hydrophobic and hydrophilic ILs were contact pin‐printed onto as‐prepared, hydrogen‐passivated porous silicon (ap‐pSi) and then the individual IL spot size, shape and associated pSi surface chemistry was determined (see figure). The results illustrate a pathway to create optical sensors based on IL/pSi microarrays for simultaneous multianalyte detection of gaseous analytes.